PENGARUH KUALITAS PRODUK, IKLAN DAN CITRA MEREK TERHADAP MINAT BELI SMARTPHONE OPPO: Studi Pada Wilayah Rw 01 Kelurahan Cinere - Lestari Fitriani Silaban, - (2019)
This research is a quantitative research that aims to determine the influence product quality, advertising, and brand image on Purchase Intention. The Population in this study the community of Kelurahan Cinere Rw. 01. The sample size was taken by 60 respondents, with non probability sampling method, especially purposive sampling. Data collection was done through questionnaire distribution. Analytical technique used is the method of analysis PLS (Partial Least Square) with SmartPLS3.0 software. The results of this study showed that (1) product quality has a significant effect on purchase intention with coefficient value of 0,433. (2) advertising has significant on purchase intention with coefficient value of 0,333. (3) brand image has significant influence on purchase intention with coefficient value of 0,260. The highest contribution is on the influence between product quality of purchase intention with coefficient value of 0,433.